Engineering Grain Boundaries in Cu2ZnSnSe4 for Better Cell Performance: A First‐Principle Study. Issue 1 (14th August 2013) - Yin, Wan‐Jian; Wu, Yelong; Wei, Su‐Huai; Noufi, Rommel; Al‐Jassim, Mowafak M.; Yan, Yanfa
<x xml:space="preserve">Abstract</x> Through first‐principle density functional theory (DFT) calculations, the atomic structure and electronic properties of intrinsic and passivated Σ3 (114) grain boundaries (GBs) in Cu2ZnSnSe4 (CZTSe) are studied. Intrinsic GBs in CZTSe create localized deep states within the band gap and thus act as Shockley‐Read‐Hall recombination centers, which are detrimental to cell performance. Defects, such as ZnSn (Zn atoms on Sn sites), Na+i (interstitial Na ions), and OSe (O atoms on Se sites), prefer to segregate into GBs in CZTSe. The segregation of these defects at GBs exhibit two beneficial effects: 1) eliminating the deep gap states via wrong bonds breaking or weakening at GBs, making GBs electrically benign; and 2) creating hole barriers and electron sinkers, promoting effective charge separation at GBs. The results suggest a unique chemical approach for engineering GBs in CZTSe to achieve improved cell performance.